Effectiveness of Regular Versus Glargine Insulin in Stable Critical Care Patients Receiving Parenteral Nutrition: A Randomized Controlled Trial. Issue 2 (February 2015) - Oghazian, Mohammad Bagher; Javadi, Mohammad Reza; Radfar, Mania; Torkamandi, Hassan; Sadeghi, Mostafa; Hayatshahi, Alireza; Gholami, Kheirollah
<x xml:space="preserve">Abstract</x> Study Objective To compare the effectiveness and safety of two glycemic control regimens in stable critical care patients receiving parenteral nutrition (PN). Design Prospective, randomized open‐label clinical trial. Methods Eligible postoperative critical care patients in the ICU began PN on the first to the seventh day of ICU admission. The PN admixture included regular insulin, in doses sufficient to maintain 3 or more goal blood glucose (BG) levels between 110 and 180 mg/dl. After 3 to 5 days of PN containing regular insulin, patients were randomized to 3 more days of regular insulin at the same dose or 80% of their total daily regular insulin dose provided in PN solution as glargine insulin. Capillary BG monitoring was performed every 6 hours. Results Twenty one patients were randomized to each treatment group. Median APACHE II scores were not significantly different between the two groups within the first 24‐hour of ICU admission. There were no significant differences between the two groups at day 3 for mean daily dextrose (306.9 ± 46.2 vs. 305.2 ± 52.2 g; p=0.913) or insulin (18.3 ± 8.8 vs. 19.5 ± 10.0 units; p=0.696) doses. The percentage of BG values in the goal (110–180 mg/dl), hyperglycemic (> 180 mg/dl), and hypoglycemic (< 70 mg/dl) BG levels were similar between the two groups (69.0% vs. 66.7%, p=0.567; 11.9% vs. 11.1%, p=0.780; 0% vs. 1.6%, p=0.124, respectively). Mean daily BG levels were not significantly different between the two groups on each of the 3 study days (day 1: 140 ± 20 vs. 131 ± 25 mg/dl, p=0.194; day 2: 136 ± 20 vs. 140 ± 18 mg/dl, p=0.498; day 3: 142 ± 15 vs. 140 ± 19 mg/dl; p=0.741). Conclusion These data suggest that, compared with regular insulin added to PN, glargine insulin results in similar glycemic control and rates of hyperglycemia and hypoglycemia in stable critical care patients.